Repeat cytoreductive surgery with or without intraperitoneal chemotherapy for recurrent epithelial appendiceal neoplasms. Issue 3 (5th February 2020) - Karpes, J. B.; Lansom, J. D.; Alshahrani, M.; Parikh, R.; Shamavonian, R.; Alzahrani, N. A.; Liauw, W.; Morris, D. L.
Abstract : Background: With recurrence rates after primary cytoreductive surgery (CRS) in excess of 50 per cent, repeat CRS is being performed increasingly, but survival outcomes have not been reported widely. This study examined the outcomes following repeat CRS for appendiceal cancer with peritoneal surface malignancy (PSM), and evaluated its feasibility and safety. Methods: A retrospective cohort of patients who had surgery between 1996 and 2018 were analysed. Patients who underwent a single CRS procedure with or without heated intraperitoneal chemotherapy (HIPEC) were compared with those who had multiple procedures with or without HIPEC. Perioperative morbidity and survival outcomes were analysed. Results: Some 462 patients were reviewed, 102 of whom had repeat procedures. For high‐grade tumours, patients who had a single CRS procedure had significantly reduced overall survival (OS) compared with those who had repeat CRS (55·6 versus 90·7 months respectively; P = 0·016). For low‐grade tumours, there was no difference in OS ( P = 0·153). When patients who had a single procedure were compared with those who had multiple procedures, there was no significant difference in major morbidity ( P = 0·441) or in‐hospital mortality ( P = 0·080). For multiple procedures, no differences were found in major morbidity ( P = 0·262) or in‐hospital mortality ( P = 0·502) when the first procedure was compared with the second. For low‐grade cancers, the peritoneal carcinomatosis index was a significant prognostic factor for OS (hazard ratio (HR) 1·11, 95 per cent c.i. 1·05 to 1·17; P < 0·001), whereas for high‐grade cancers repeat CRS (HR 0·57, 0·33 to 0·95; P = 0·033), complete cytoreduction score (HR 1·55, 1·01 to 2·40; P = 0·046) and presence of signet ring cells (HR 2·77, 1·78 to 4·30; P < 0·001) were all significant indicators of long‐term survival. Conclusion: In selected patients presenting with PSM from epithelial appendiceal neoplasms, repeat CRS performed in high‐volume centres could provide survival benefits. Abstract : Cytoreductive surgery (CRS) has been established as the standard for the management of peritoneal surface malignancy (PSM); however, the utility of repeat CRS for recurrent epithelial appendiceal neoplasms has not been explored widely. A large retrospective cohort analysis was performed of patients with PSM of appendiceal origin, evaluating the short‐ and long‐term outcomes. The findings showed that, with careful patient selection, repeat CRS for PSM of appendiceal origin can result in long‐term survival with acceptable morbidity. Citoreductive surgery in peritoneal malignancy fro appendiceal neoplasm Abstract : Antecedentes: En países de bajos y medianos ingresos ( low‐ and middle‐income countries, LMIC) hay que desarrollar estrategias de futuro para incrementar la disponibilidad de equipos quirúrgicos, adquisición, capacitación, uso, mantenimiento y complicaciones relacionadas con las unidades electroquirúrgicas ( electrosurgical unit, ESU) y los equipos de laparoscopia. Métodos: Se realizó una encuesta entre los cirujanos que asistieron a la reunión anual del Colegio de Cirujanos de África Oriental, Central y Meridional ( College Of Surgeons of East, Central and Southern Africa, COSECSA) en diciembre de 2017 y a la reunión anual de la Sociedad Quirúrgica de Kenia ( Surgical Society of Kenya, SSK) en marzo de 2018. Se encuestaron también a los técnicos de equipos biomédicos ( Biomedical Equipment Technicians, BMET) y se recopilaron los registros de mantenimiento en Kenia entre febrero y marzo de 2018. Resultados: Participaron 80 sujetos, 59 cirujanos de 11 países africanos y 21 BMET de Kenia. Se recopilaron 36 registros de mantenimiento. Todos los cirujanos de COSECSA y SSK disponían de ESU, pero menos de la mitad (49%) disponían de equipos de laparoscopia. Como principales problemas se detectaron la reutilización de accesorios desechables en las ESU y las dificultades para disponer de CO2. Más de las tres cuartas partes (78%) de los cirujanos contaban con equipos de mantenimiento para las ESU, pero solo el 59% disponía de mantenimiento para los equipos de laparoscopia en su centro. Conclusión: A pesar de la disponibilidad de equipos quirúrgicos, en estos LMIC se detectaron serias dificultades en su mantenimiento, hecho que limita la implementación de la cirugía abierta y laparoscópica.